MIKC-Type MADS-box Genes Regulate Phytohormone-Dependent Fruit Ripening in Tomatoes - Changxia Li; Yushi Lu; Junrong Xu; Jing Cui; Yunzhi Liu; Wenjin Yu (Horticulturae)
Tomato fruit ripening is a complex process that determines the formation of fruit quality. Transcription factors (TFs) play key roles in regulating fruit ripening and quality formation. MADS-box genes, a crucial class of genes involved in virtually all aspects of plant development, are regarded as important candidate members among them. In this study, we present a detailed overview of the phylogeny and expression of 32 tomato MIKC-type MADS-box genes. Moreover, 20 genes contained many phytohormone-related elements. In combination with higher expression in fruit, eight genes are suggested to be involved in plant hormone pathways that regulate fruit ripening. A virus-induced gene silencing (VIGS) experiment revealed that TM4, TAGL11, SlMADS6, SlMADS99, TAGL1, SlMADS1, RIN, and MC may positively regulate fruit ripening. Measurements of the endogenous phytohormones in silenced TM4, TAGL11, SlMADS6, SlMADS99, TAGL1, SlMADS1, RIN, or MC fruit suggest that eight MIKC-type MADS-box genes, as well as medicated abscisic acid (ABA), salicylic acid (SA), gibberellin (GA3), indole-3-acetic acid (IAA), and/or methyl jasmonate (MeJA) pathways, positively regulate fruit ripening in tomatoes.